Analisis Manajemen Likuiditas dan Manajemen Gap pada Perbankan Syariah yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022 - Musnawati, Musnawati; Nurnasrina, Nurnasrina; Syahpawi, Syahpawi (MUI Kota Pekanbaru, 2024)
Indonesia's economy is driven by various sectors, with the banking sector playing a very important role. Indonesian banking has been operating since colonial times until today, functioning as a liaison between capital owners and capital managers. Capital owners often do not have sufficient skills to manage funds professionally, while banks have these abilities, so they can manage funds optimally and foster trust. In management, banks place the use of funds as assets and the source of funds as liabilities, which is in accordance with macro monetary policy in a country's asset management. The main purpose of this management is to monitor the financial position, which is important for planning, organizing, and supervising, as well as for capital, fund raising, fund use, and financing in liquidity management. Interest rates greatly affect liquidity management, because they have a difference or difference to sensitive assets and liabilities. Good liquidity management maintains a balance between assets and liabilities to meet various financial obligations, including debt repayments and employee salaries. The case of Silicon Valley Bank, which collapsed in March 2023, shows the importance of healthy liquidity ratios. A rapid rise in interest rates lowers the value of bonds in the portfolio and increases the cost of credit, which creates a GAP in profit returns. In contrast to conventional banking, Islamic banking uses a profit-sharing system that is more flexible in profit returns. This phenomenon attracts the author's attention to further discuss liquidity management and GAP management in Islamic banking listed on the Indonesia Stock Exchange for the 2019-2022 period, where there are four Islamic banks that have been listed on the Islamic stock exchange.